Germination Ecology of Arundinaria alpina (K. Schum.) and Oxytenanthera abyssinica (A. Rich.) Munro Seeds: Indigenous Bamboo Species in Ethiopia. (17th November 2015) - Bahru, Tinsae; Mulatu, Yigardu; Kidane, Berhane
Abstract : Highland bamboo ( Arundinaria alpina ) and lowland bamboo ( Oxytenanthera abyssinica ) are indigenous to Ethiopia and endemic to Africa. Seeds of A. alpina were collected from Dawa Wereda (District), while O. abyssinica seeds were collected from Pawe and Sherkole Weredas. In this study, seed presowing treatments, effects of dry heat, moist heat, and light/dark treatments on the germination of seeds were tested. The averages were of 59, 416 and 8, 393 seeds contained within 1 kg of A. alpina and O. abyssinica seeds within 86 and 91% pure seeds, respectively. From 1 kg of pure seeds 37, 301 and 7, 168 seedlings are raised in the laboratory in their respective orders. The result revealed that control seeds of A. alpina and O. abyssinica showed the best germination of 73 and 98%. Germination of both dry and moist heat treatments of O. abyssinica seeds was significantly improved at 60 and 80°C. Unlike A. alpina seeds, seeds of O. abyssinica had better germination for light treatment compared to dark. For effective large scale plantation and raising of A. alpina and O. abyssinica seedlings from its seeds for laboratory, control seeds supply to necessary light source (for O. abyssinica seeds) is recommended.